Movimentos sociais@internet e sua dimensão educativa - Menezes, Maurelio (2015)
This paper presents results of a survey in which it was intended to understand the educational dimension of a phenomenon emerged in the last two years, virtual social movements, so-called because they use the internet as a mobilization tool. For this, we analyzed various movements that fit this profile, and especially the movement that became known as the Arab Spring and the series of demonstrations in Brazil in 2013, this adjective as "Fall-Winter Brazilian". He served as a starting point, the view of the Italian Marxist thinker Antonio Gramsci (1891-1937) on education as a promoter of emancipation of the masses. The methodological instruments used were participant observation in the demonstrations held in Mato Grosso, the monitoring of local and national news about the other, occurred in other states, monitoring of international news about the Arab Spring interviews as well as bibliographic and documentary research on both manifestations. The bibliographical and documentary research was based on a threefold agenda: A) the writings of and about the Italian philosopher published or reproduced by print and digital media, B) the writings on the social movements since the 1920s when it restricted the proletarian movement and party, through the 1960s when they won more space as academic study to the present day; C) the writings on internet / virtual social movements, so-called because they use intensively as mobilization tool social media. Research on the movement took also based on interviews and academic and journalistic articles, in addition to research conducted by universities, institutes and national and international agencies. As shown search results even before the social movements focused here, the Internet has served as a means of mobilization and indignation. Today, however, both the Arab Spring as the manifestations of the Fall-Winter Brazilian indicate clearly the driving force of internáutics networks, which leads to consideration of the potential organizational strength of virtual social movements.